Effect of sodium monensin and cinnamaldehyde on the growth and phenotypic characteristics of Prevotella bryantii and Prevotella ruminicola - Ferme, D; Malnersic, M; Lipoglavsek, L; Kamel, C; Avgustin, G (Folia microbiologica, 2008)
Two representative strains of Gram-negative rumen bacteria from the genus Prevotella were used as model organisms in order to evaluate the effect of cinnamaldehyde (the secondary metabolite found in extracts of the Cinnamomum family) vs. sodium monensin on growth, cell size and cell protein production. Prevotella bryantii B(1)4 was found to be remarkably more resistant to the action of both compounds than Prevotella ruminicola 23. The approximate IC(50) concentrations of sodium monensin influenced the increase in cell size of both strains during growth, which was much more pronounced in the case of the B(1)4 strain. A similar effect was observed in strain B(1)4 when 1.438 mmol/L cinnamaldehyde was added to the growth medium, indicating a possible interference with cell division. The action of cinnamaldehyde on P. bryantii B(1)4 was concentration-dependent, in contrast to the effect observed on P. ruminicola 23.
Keywords: Prevotella ruminicola; bachor; antiprotozoální látky; Monensin; Rumen; monensin; parazitické testy citlivosti; Prevotella; fenotyp; inhibiční koncentrace 50; Acrolein; Animals; Antiprotozoal Agents; Phenotype; akrolein; Inhibitory Concentration 50; zvířata; Parasitic Sensitivity Tests